HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN STATUS GIZI SELAMA KEHAMILAN DI PUSKESMAS BAHU KOTA MANADO - Goni, Anastasia P. G.; Laoh, Joice M.; Pangemanan, Damajanty H. C. (JURNAL KEPERAWATAN)
Abstract: In general, the causes of malnutrition in pregnant women due to the consumption of foods that do not meet the nutrition requirements. Nutritional is a measure of the success of nutrition for pregnant women. WHO (World Health Organization) recommends an additional amount of 150 kcal a day in the first trimester and 350 kcal a day in the second and third trimester. Low levels of knowledge mother does not understand how to lead fulfilling necessary nutrients pregnant women during pregnancy (Depkes RI, 2002). Nutritional needs during pregnancy will increase per day, despite all the Indonesian people already know the benefits of nutrition for pregnant women, but until now there are many pregnant women who have nutritional problems (Damanik, 2009). The purpose of this study to determine the relationship of knowledge and attitudes of pregnant women with nutritional status during pregnancy on the health center Bahu Manado City. Design of this study used cross sectional method. The population is client pregnant women prenatal care at the health center came Bahu Manado City. The samples in this study were pregnant women at health center clients at Puskesmas Bahu Manado as many as 40 people who have fulfilled the inclusion criteria. The sampling technique used was purposive sampling. Instrument used was a questionnaire and measuring Antrhopometri. Data analysis using SPSS version 16, with Spearman'rho test to determine the relationship of knowledge and attitudes of pregnant women with nutritional status. Conclusion knowledge of the nutritional of pregnant women have gained value relationship (p = 0.000 <α0,05) and the attitude of the nutritional of pregnant women have gained value relationship (p = 0.003 <α0,05). Adviceishavea lot of counseling and information for pregnant women to knowledge ful fill mentnutritional status during pregnancy. Keywords: Maternal Knowledge, Attitude Pregnant Women, Nutrional During Pregnancy. Abstrak: Secara umum penyebab kekurangan gizi pada ibu hamil karena konsumsi makanan yang tidak memenuhi syarat pemenuhan gizi. Status gizi merupakan ukuran keberhasilan dalam pemenuhan nutrisi untuk ibu hamil. WHO (World Health Organization) menganjurkan jumlah tambahan sebesar 150 Kkal sehari pada trimester I, dan 350 Kkal sehari pada trimester II dan III. Tingkat pengetahuan yang rendah menyebabkan ibu tidak mengerti cara pemenuhan nutrisi yang dibutuhkan ibu hamil selama kehamilannya (Depkes RI, 2002). Kebutuhan gizi selama kehamilan akan meningkat perhari, meskipun semua orang Indonesia sudah mengetahui manfaat gizi bagi ibu hamil namun sampai saat ini masih banyak ibu hamil yang mengalami masalah gizi (Damanik, 2009). Tujuan penelitian ini untuk mengetahui hubungan pengetahuan dan sikap ibu hamil dengan status gizi selama kehamilan di Puskesmas Bahu Kota Manado. Desain penelitian ini menggunakan metode Cross Sectional. Populasi dalam penelitian ini adalah klien ibu hamil yang datang memeriksakan kehamilan di Puskesmas Bahu Kota Manado. Sampel dalam penelitian ini adalah klien ibu hamil di Puskesmas Bahu Kota Manado sebanyak 40 orang yang telah memnuhi kriteria inklusi. Teknik pengambilan sampel yang digunakan adalah Purposive Sampling. Instrument yang digunakan adalah kuesioner dan pengukuran Antrhopometri. Analisis data menggunakan SPSS versi 16, dengan uji Spearman’rho untuk mengetahui hubungan pengetahuan dan sikap ibu hamil dengan status gizi. Kesimpulan ialah pengetahuan ibu hamil dengan status gizi mempunyai hubungan diperoleh nilai (p=0,000 <α0,05) dan sikap ibu hamil dengan status gizi mempunyai hubungan diperoleh nilai (p=0,003 <α0,05). Saran ialah harus banyak penyuluhan dan informasi pada ibu hamil untuk pengetahuan pemenuhan status gizi selama kehamilan. Kata kunci: Pengetahuan Ibu Hamil, Sikap Ibu Hamil, Status Gizi Selama Kehamilan